2003
DOI: 10.1044/1092-4388(2003/034)
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Normalization for Inter- and Intratalker Variation in Cantonese Level Tones

Abstract: Inter- and intratalker variation in the production of lexical tones may contribute to acoustic overlap among tone categories. The present study investigated whether such category overlap gives rise to perceptual ambiguity and, if so, whether listeners are able to reduce this ambiguity using contextual information. In the first experiment, native Cantonese-speaking listeners were asked to identify isolated Cantonese level tones produced by 7 talkers. Identification accuracy was significantly higher when the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(174 citation statements)
references
References 15 publications
14
159
1
Order By: Relevance
“…Those category boundaries that are not defined in terms of the location of regions of naturally heightened auditory sensitivity appear to be defined in a talkerdependent manner. The results presented by Wong and Diehl (2003) showed that Cantonese listeners are strongly influenced by contextual information when making level tone category decisions, providing a basis for the observation that listeners have difficulty identifying level tone categories presented in isolation. The differences observed here between the discrimination performance predicted by the level tone identificationtask in and out of context (see Figure 5) strongly support this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Those category boundaries that are not defined in terms of the location of regions of naturally heightened auditory sensitivity appear to be defined in a talkerdependent manner. The results presented by Wong and Diehl (2003) showed that Cantonese listeners are strongly influenced by contextual information when making level tone category decisions, providing a basis for the observation that listeners have difficulty identifying level tone categories presented in isolation. The differences observed here between the discrimination performance predicted by the level tone identificationtask in and out of context (see Figure 5) strongly support this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…When a speech signal enters the auditory system, spectro-temporal characteristics of the signal are processed to extract the linguistic information (see the first arrow in Figure 5). Acoustic parameters carrying talker information such as F0, F3 and voice quality will be analyzed (Green, Tomiak, & Kuhl, 1997;Kaganovich, Francis, & Melara, 2006;Magnuson & Nusbaum, 2007;Mullennix & 35 Pisoni, 1990;Mullennix, Pisoni, & Martin, 1989;Nusbaum & Magnuson, 1997;Nusbaum & Morin, 1992;Wong & Diehl, 2003;Wong, Nusbaum, & Small, 2004;Zhang, Pugh, Mencl, Molfese, Frost, Magnuson, Peng, & Wang, 2016). The analyzed talker characteristics are likely checked against learned talker models stored in memory to see if the characteristics match any familiar talkers.…”
Section: General Discussion: a New Model Of Talker Normalizationmentioning
confidence: 99%
“…There is plenty of evidence that listeners estimate the location/identity of a lexical tone according to the distribution of a talker's speaking F0 in a speech context (Chen & Peng, 2015;Francis, Ciocca, Wong, Leung, & Chu, 2006;Huang & Holt, 2009;Leather, 1983;Lin & Wang, 1984;Moore & Jongman, 1997;Wong & Diehl, 2003;Zhang et al, 2012Zhang et al, , 2013. Lin and Wang (1984) investigated how the relative F0 height of a single-word context affected the perception of Mandarin tones.…”
Section: Extrinsic Normalizationmentioning
confidence: 99%
“…Lexical tone perception research has mainly focused on psychological processes (Xu, 1994;Wong and Diehl, 2003) and gross hemispheric specialization (Gandour et al, 1997). Recently, several neuroimaging studies have been conducted (Gandour et al, 2000) and reported activations in left inferior frontal regions.…”
Section: Introductionmentioning
confidence: 99%